EDUKASI KUALITAS DAN KEAMANAN KONSUMSI MADU PADA MASYARAKAT LAMBARA SULAWESI TENGAH - Utami; Israh; Rumambi, Farha (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
Honey as a natural product is widely utilized, often facing challenges related to its quality and safety that affect public health. This service aims to provide a better understanding and improve the quality of life of the community in Lambara Village by encouraging the consumption of safer and quality-assured honey and encouraging active community participation in maintaining and producing high-quality honey. So that the potential and opportunity to improve the quality of life from both economic and health aspects can be realized. As a result of this activity, the community of Lambara Village can understand the importance of recognizing the characteristics of quality honey and proper storage methods to maintain its safety and can be utilized as a source of income that is guaranteed in quality.